Evaluación de la protección catódica por corriente impresa para metales en suelos amazónicos de alta agresividad química - García Ahuanari, Nestor Miguel (2026)
The present research aimed to evaluate the efficiency of an impressed current cathodic protection (ICCP) system to reduce the corrosion rate of metals exposed to highly chemically aggressive Amazonian soils. The study was conducted at the General and Inorganic Chemistry Laboratory of the Faculty of Chemical Engineering at the National University of the Peruvian Amazon, using a unifactorial experimental design with seven treatments corresponding to six current density levels (10, 25, 50, 100, 150, and 200 mA/m²) plus a control group without protection. ASTM A-36 steel specimens measuring 100 mm × 50 mm × 1 mm were used, submerged in Amazonian soil from a petroleum zone, characterized by pH 6.0 and electrical conductivity of 345 μS/cm. The tests were conducted in hermetically sealed 4-liter buckets over a continuous three-month period. The corrosion rate was determined using the gravimetric mass loss method according to ASTM G1 standard. The results demonstrated that the control sample (without protection) exhibited a corrosion rate of 53.89 μm/year, while the application of impressed current significantly reduced this value. The optimal current density was established at 150 mA/m², achieving a protection efficiency of 94.1% with a residual corrosion rate of 3.18 μm/year. An inversely proportional relationship was observed between applied current density and corrosion rate, with a coefficient of determination R² = 0.9847. It is concluded that impressed current cathodic protection is highly effective for mitigating corrosion of buried metallic structures in highly chemically aggressive Amazonian soils.